Development and Evaluation of the MARVOCAB Application for Enhancing Maritime Vocabulary Acquisition - Rohmah, Nur; Suswati, Elis; Taufikurrahman, Mohammad Rafli; Prasetianto, Torie Adhi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aimed to develop and evaluate the effectiveness of the MARVOCAB application in improving maritime vocabulary acquisition among students at Politeknik Ilmu Pelayaran Semarang. Many students face challenges in mastering maritime terminology, which negatively impacts their academic performance and their preparedness for professional communication within the maritime industry. The study employed a Research and Development (R&D) methodology, encompassing the stages of Planning, Production, and Evaluation. The sample consisted of cadets from the Politeknik Ilmu Pelayaran Semarang. The application was designed with key features, including system modeling, database construction, user interface development, and was followed by implementation and black-box testing to ensure functionality and usability. The effectiveness of the MARVOCAB application was assessed using the N-gain score, a measure of learning improvement. The results demonstrated a high level of effectiveness, with an average N-gain score of 0.77, indicating a substantial improvement in students’ maritime vocabulary acquisition. These findings suggest that the MARVOCAB application significantly enhances students' comprehension of maritime-specific terminology and holds strong potential for integration into maritime education curricula. The results indicate that technology-assisted vocabulary learning tools can address domain-specific language gaps effectively, supporting learners’ academic and professional readiness